PENERAPAN PRINSIP GOOD GOVERNANCE DALAM PELAYANAN PUBLIK PADA KANTOR KECAMATAN SOKOBANAH - Saputra, Faroyhan Vicky; Supriyo, Agus (PALAR (Pakuan Law review), 2024)
AbstractThe aim of this research is to explain that a country is a region that has a system or rules that apply to every individual. Along with the development of democracy, a policy has also developed which is called good government or what we know as good governance. In terms of good governance, there are several principles for managing good governance, namely transparency, accountability, responsibility, independence and fairness. The existence of several of these principles certainly improves public services. According to Law Number 25 of 2009 concerning Public Services, it is an activity or series of activities in order to fulfill service needs in accordance with statutory regulations for every citizen and resident regarding goods, services and/or administrative services provided by public service providers. Specifically in this case at the Sokobanah District Office, Sampang Regency, the implementation of good governance principles in the Sokobanah subdistrict government has been carried out well but is still experiencing obstacles due to several factors which hinder the implementation of the good governance principles in the Sokobanah subdistrict. Key words: good governance, principles of public service, Sokobanah sub-district AbstrakTujuan Penelitian ini ialah untuk menjelaskan bahwa Negara merupakan suatu wilayah yang memiliki suatu sistem atau aturan yang berlaku bagi setiap individu. Seiring dengan berkembangnya demokrasi, juga berkembang sebuah kebijakan yang disebut dengan istilah good government atau yang kita kenal dengan tata pemerintahan yang baik. Dalam istilah good governance ada beberapa prinsip untuk menata pemerintahan yang baik yaitu transparansi, akuntabilitas, responsibilitas, independent dan fairness. Adanya beberapa prinsip-prinsip tersebut tentu untuk meningkatkan pelayanan publik. Menurut Undang-Undang Nomor 25 Tahun 2009 tentang Pelayanan Publik adalah kegiatan atau rangkaian kegiatan dalam rangka pemenuhan kebutuhan pelayanan sesuai dengan peraturan perundang-undangan bagi setiap warga negara dan penduduk atas barang, jasa, dan/atau pelayanan administratif yang disediakan oleh penyelenggara pelayanan publik. Khususnya dalam hal ini pada Kantor Kecamatan Sokobanah Kabupaten Sampang bahwa implementasi prinsip good governance pada pemerintah kecamatan sokobanah sudah dilakukan dengan baik namun masih mengalami kendala oleh beberapa faktor yang menjadi penghambat terlaksananya proses pelaksanaan prinsip-prinsip good governance dikecamatan sokobanah.  Kata kunci: good governance, prinsip pelayanan publik, kecamatan sokobanah